A Slow Impossible Mirror Picture. (December 2020) - Casati, Roberto; Varzi, Achille C.
A new type of impossible picture is presented and described. The picture involves an object along with its reflection in a plane mirror, delivering two apparently irreconcilable views of the object itself when seen simultaneously in its flesh and in the mirror. Contrary to other, more familiar impossible pictures, its interpretation requires explicit reasoning about the represented reality. It is a slow impossible picture.